Ukrainian Adaptation of the Brief-COPE Questionnaire - Yablonska Tetiana; Vernyk Oleksiy; Haivoronskyi Hlib (Insight: the psychological dimensions of society, 2023)
The purpose of the research was to adapt the Brief-COPE (Carver et al., 1997) into Ukrainian. In the currentconditions of military aggression, it is increasinglyimportant to study its consequences for the mentalhealth of millions of Ukrainians, in particular, to investigate strategies for overcoming stress, which willallow developing effective methods of psychologicalassistance. The Ukrainian version of the Brief-COPE(Carver et al., 1997), which is widely used worldwide,will give the opportunity to use it practically in psychodiagnostics,as well as the possibility of conductingcomparative studies. Methods. The Brief-COPEquestionnaire was translated from English into Ukrainianby two bilingual psychologists using the reversetranslation method. The study sample consistedof 192 respondents aged 17 to 44 years (M=23.12,SD=6.32), mostly students and young working adults.The survey was conducted through the online serviceGoogle Forms. The respondents were offered a situationalversion of the methodology; the retest took place10-45 days after the test. Also, the respondents wereoffered the Stress Coping Inventory (SVF120, Jankeet al, 1985) in the adaptation of N. Vodopianova. Thedata were analyzed using statistical data processingpackages SPSS, JAMOVI; the following methods wereused: descriptive statistics, scale reliability analysis,confirmatory factor analysis (CFA), exploratory factoranalysis (EFA) and correlation analysis (Spearman’scoefficient). Reliability was investigated onthe basis of Cronbach’s model with the calculationof the alpha coefficient of consistency. Results. Theresults of the study indicate a fairly good consistencyof the data obtained with the basic theoretical modelof the methodology, with the exception of some scales,which correspond to the data of foreign studies oncertain controversy of the factor structure of the Brief-COPE. The content validity test revealed a significantnumber of strong correlations. A high level of test-retestreliability of the adapted tool has been revealed.The results of the obtained data are compared withthe data of foreign studies using Brief-COPE. Discussionand conclusions. The test of the psychometriccharacteristics of the Ukrainian version of the BriefCOPE inventory (Carver, 1997) showed a fairly highinternal validity and reliability of the adapted methodology.Thus, it can be argued that the Ukrainian versionof the Brief COPE inventory (Carver, 1997) can be usedin studies to measure an individual’s coping behavior.